(untitled) (Revista Apotheke, 2018)
Based on the notion about art shaped on European thought, this paper develops a critical approach to the binomial art/non-art. This notion has been expanded during the colonization processes, in the Modern period. So, the purpose of this reflection is to outline some parameters for a poetic of solidarity, based on the nature of the relationship between people in the exercise of creating processes and sharing.